EuDiS - A comprehensive database of the seed dispersal syndromes of the European flora - Vargas, Pablo (2023)
Seed dispersal is a critical process in plant colonisation and demography. Fruits and seeds can be transported by several vectors (typically animals, wind and water), which may have exerted strong selective pressures on plant's morphological traits. The set of traits that favour dispersal by a specific vector have been historically considered as seed dispersal syndromes. As seed dispersal syndromes have a great potential to predict how seeds move (i.e. the relative importance of the standard mechanisms of seed dispersal), they have attracted the attention of naturalists and researchers for centuries. However, given that observations of actual dispersal events and colonisation are seldom reported, there is still much confusion in current studies failing to properly discriminate between seed dispersal syndromes (i.e. sets of traits that favour a particular mechanism) and actual seed dispersal (i.e. the vector that moves a given seed in one dispersal event). This distinction is important because the presence of any seed dispersal syndrome does not preclude the seed being occasionally dispersed by other non-standard mechanisms (i.e. different from the one predicted). Similarly, the absence of seed dispersal syndromes does not prevent seeds from being dispersed. The correct coding of seed dispersal syndromes thus requires a systematic and evolutive, rather than a phenomenological approach. Unfortunately, such approach has rarely been implemented at a community-level and no comprehensive datasets of seed dispersal syndromes are yet available for any entire flora.